Control of resistance against bacteriophage killing by a metabolic regulator in meningitis-associated Escherichia coli - Connolly, James P. R.; Turner, Natasha C. A.; Serrano, Ester; Rimbi, Patricia T.; Browning, Douglas F.; O’Boyle, Nicky; Roe, Andrew J. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Ecologically beneficial traits in bacteria are encoded by intrinsic and horizontally acquired genes. However, such traits are not universal, and the highly mosaic nature of bacterial genomes requires control at the transcriptional level to drive these processes. It has emerged that regulatory flexibility is widespread in the Escherichia coli species, whereby preexisting transcription factors can acquire new and unrelated roles in regulating beneficial traits. DsdC is the regulator of D-serine tolerance in E. coli, is essential for D-serine catabolism, and is often encoded by two copies in neonatal meningitis–associated E. coli (NMEC). Here, we reveal that DsdC is a global regulator of transcription in NMEC and does not require D-serine for the control of novel beneficial traits. We show that DsdC binds the chromosome in an unusual manner, with many binding sites arranged in clusters spanning entire operons and within gene coding sequences, such as neuO. Importantly, we identify neuO as the most significantly down-regulated gene in a strain deleted for both dsdC copies, in both the presence and absence of D-serine. NeuO is prophage encoded in several NMEC K1 isolates and mediates capsule O-acetylation but has no effect on attachment to or invasion of human brain endothelial cells. Instead, we demonstrate that NeuO provides resistance against K1 bacteriophage attack and that this critical function is regulated by DsdC. This work highlights how a horizontally acquired enzyme that functions in cell-surface modulation can be controlled by an intrinsic regulator to provide a key ecological benefit to an E. coli pathotype.